Implication of Monoclonal Antibody for COVID-19 Treatment - Tuladhar, Reshma (Journal of Institute of Science and Technology, 2020)
Coronavirus induced disease-19 (COVID-19) pandemic affecting the entire world has continued to pose threat despite nearly a year of its onset. With more than 50 vaccine candidates targeting COVID-19 on trials and 15 at the final stage of testing, wide availability to the general public is still a long way to go. Thus alternative therapeutics is in the progress to minimize the effect of COVID-19. This systematic review evaluated the articles related to immunotherapy for COVID19. PubMed database was used to search for keywords; COVID-19, immunotherapy, and monoclonal antibody for relevant publications of the year 2020. The review was performed based on PRISMA protocol and the final 20 articles were included in the final review. These studies demonstrated that Tocilizumab, the monoclonal antibody that blocks IL6 receptors has improved outcomes in COVID-19 infected patients.